High mortality rate in cancer patients with symptoms of COVID-19 with or without detectable SARS-COV-2 on RT-PCR - Assaad, Souad; Avrillon, Virginie; Fournier, Marie-Line; Mastroianni, Benedicte; Russias, Bruno; Swalduz, Aurélie; Cassier, Philippe; Eberst, Lauriane; Steineur, Marie-Pierre; Kazes, Marianne; Perol, Maurice; Michallet, Anne-Sophie; et al. (European journal of cancer (1990), 2020)
Cancer patients presenting with COVID-19 have a high risk of death. In this work, predictive factors for survival in cancer patients with suspected SARS-COV-2 infection were investigated. PRE-COVID-19 is a retrospective study of all 302 cancer patients presenting to this institute with a suspicion of COVID-19 from March 1st to April 25th 2020. Data were collected using a web-based tool within electronic patient record approved by the Institutional Review Board. Patient characteristics symptoms and survival were collected and compared in SARS-COV-2 real-time or reverse-transcriptase PCR (RT-PCR)–positive and RT-PCR–negative patients. Fifty-five of the 302 (18.2%) patients with suspected COVID-19 had detectable SARS-COV-2 with RT-PCR in nasopharyngeal samples. RT-PCR–positive patients were older, had more frequently haematological malignancies, respiratory symptoms and suspected COVID-19 pneumonia of computed tomography (CT) scan. However, respectively, 38% and 20% of SARS-COV-2 RT-PCR–negative patients presented similar respiratory symptoms and CT scan images. Thirty of the 302 (9.9%) patients died during the observation period, including 24 (80%) with advanced disease. At the median follow-up of 25 days after the first symptoms, the death rate in RT-PCR–positive and RT-PCR–negative patients were 21% and 10%, respectively. In both groups, independent risk factors for death were male gender, Karnofsky performance status <60, cancer in relapse and respiratory symptoms. Detection of SARS-COV-2 on RT-PCR was not associated with an increased death rate (p = 0.10). None of the treatment given in the previous month (including cytotoxics, PD1 Ab, anti-CD20, VEGFR2…) correlated with survival. The survival of RT-PCR–positive and –negative patients with respiratory symptoms and/or COVID-19 type pneumonia on CT scan was similar with a 18.4% and 19.7% death rate at day 25. Most (22/30, 73%) cancer patients dying during this period were RT-PCR negative. The 30-day death rate of cancer patients with or without documented SARS-COV-2 infection is poor, but the majority of deaths occur in RT-PCR–negative patients. •Cancer patients with SARS-COV-2 real-time or reverse-transcriptase PCR (RT-PCR have a death rate of 20% at 30 days.•Cancer patients with clinical symptoms of COVID-19 but SARS-COV-2 RT-PCR have high death rate.•70% cancer patients suspected COVID-19 dying before day 30 have no SARS-COV-2 on RT-PCR or computed tomography.•For both groups, the risk factors of death include "relapsing cancer", Karnofsky performance status <60, male gender, lymphopenia, and high CRP levels.•PD1 Ab, anti-CD20 and antiangiogenic treatments do not correlate with risk of death.